Application of Newman’s Error Analysis to Identify Students’ Errors in Solving Fraction Problems - Payung, Zatman; Kusumah, Yaya Sukjaya; Mulyaning, Endang Cahya; Avip, Bambang (IKIP Siliwangi, 2025)
Mathematics is a subject that has been taught since elementary school with the aim of training students to think critically, logically, systematically, and solve problems. In fact, many students experience difficulties in learning mathematics, especially in fractional material This study aims to identify mistakes made by elementary school students in solving fractional problems using Newman's Error Analysis (NEA). Through a descriptive qualitative approach, this study analyzes the results of student work on fractional questions based on five stages of NEA: reading error, comprehension error, transformation error, process skills error, and encoding error). Data was collected through written tests and interviews, involving students from UPI Laboratory Elementary School, Pelita Bangsa Elementary School, and SDN 272 Sukasari. Student errors are then grouped by NEA stages to identify the most mistakes made by students. The results of the study showed that students made mistakes at all stages of the NEA. The most common mistakes experienced by students are at the comprehension error and process skill error stages. There are still many students who are not able to represent fractions with pictures and students also still make many mistakes in the fraction operation process. Based on the results of the research, it was concluded that students still had difficulties in fractional material by seeing the mistakes made by students when working on fractional problems. It is necessary to improve students' conceptual understanding and procedural skills in fractional materials.